The usefulness of liquid-based cytology for endoscopic ultrasound-guided tissue acquisition of solid pancreatic masses - Itonaga, Masahiro; Ashida, Reiko; Kitano, Masayuki (Frontiers in Medicine, 2022)
Liquid-based cytology (LBC) is used primarily for cervical cytology, although it is also used for analyzing liquid samples such as urine and acites specimens, as well as fine needle aspiration material, such as those obtained from breast and thyroid. The usefulness of the LBC method for endoscopic ultrasound-guided tissue acquisition (EUS-TA) of solid pancreatic masses was recently reported. The LBC method can produce multiple pathological slides and can be applied to immunocytochemistry and genetic analyses. In this article, we review the usefulness of LBC for EUS-TA of solid pancreatic masses.